Implants for surgery - skeletal pins and wires - part 2: Steinmann skeletal pins - Dimensions (ISO 5838-2:1991, MOD) - Abdul Razak, Noor Hayati; Mazani, Nor Iratul Munirah; Choon, David; Goonting, Tracy E.; T, Mahadevan; Law, Ching Yee; How, Kim Chuan; Singh, Harwant; Ismail, Zulkharnain; Manickam, Thirumal; Yaakob, Mohd Amin; Mohd Yusof, Hyzan; et al. (SIRIM, 2015)
This Malaysian Standard specifies the dimensions of Steinmann skeletal Pins. Material and mechanical requirements are covered by ISO 5838-1.